High art - Stover, Susan; Hall, Dolly; Levy-Hinte, Jeff; Cholodenko, Lisa; Sheedy, Ally; Mitchell, Radha; October Films; USA Home Entertainment (Firm) (New York, N.Y. : USA Home Entertainment, 1999)
Depicts a naive young woman whose stock rises at a pretentious art magazine because of her budding relationship with a once brilliant photographer who had a breakdown years ago. The question is how deeply Syd is willing to immerse herself in Lucy's hedonistic, heroin- infused, lesbian lifestyle
Originally released as a motion picture in 1998
Formatted to fit TV
Director of photography, Tami Reiker; editor, Amy E. Duddleston; original music, Shudder To Think
Ally Sheedy, Radha Mitchell, Tammy Grimes, Patricia Clarkson, Gabriel Mann, Anh Duong, Bill Sage, David Thornton, Rudolph Martin
Rated R
VHS; ultra-stereo, digitally recorded
Keywords: Photography, Artistic -- Drama; Love -- Drama; Interpersonal relations -- Drama; Sexual orientation -- Drama; Films for the hearing impaired; Feature films; Video recordings